Exploring the applications of deep reinforcement learning and quantum variational circuit In quantum machine learning - Saha, Prashanta Kumar; Saha, Vishal (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.